Macroeconimic dynamic model with environmental factors (on the case of Ukraine) - Меркулова, Т. В.; Томілович, О. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The aggravation of environmental problems, related to human economic activity, and the spread of the phenomenon to all (without exception) regions and states of the world determinate relevance and global dimension of this issue in these times and show the need for research on the relationship between economic development and nature change to find ways to resolve their contradiction. Economic mathematical models play a significant role in such research as they allow quantitative estimation of these interconnections and multivariate calculations in order to find effective alternatives for economic development with an environmental dimension.The objective of this study is to develop the macroeconomic dynamic model with environmental factors by modifying William Nordhaus Dynamic Integrated Climate‑Economy Model (DICE model) and test it on the data of Ukraine. This article contains the following research results: the main assumptions of the Nordhaus model were outlined; the macroeconomic dynamic model with environmental factors was developed by modifying the Nordhaus model; the parameters of the modified model were estimated on the data of Ukraine; the system‑dynamic implementation of the model was developed; experiments with the system‑dynamic implementation of the model were conducted; the results of the experiments were interpreted.The research was conducted with methods of mathematical and system‑dynamic modeling, statistical methods, econometric modeling, Vensim and Microsoft Excel programs (the Data Analysis Regression tool in particular).Based on the above, some patterns between economic development and nature changes were found, which confirmed the possibility of using the modified model for analyzing and reconciling these components.